Programmed digital poetry - Bootz, Philippe (Primerjalna književnost, 2013)
This paper examines the poetic modalities that Eduardo Kac considers to constitute media poetry, raising the question of the relevance of the term media. It comes to the conclusion that these poetic modalities can be considered elements of the same class of works, except that this class is more concerned with technotext and procedural work than with media.
Keywords: Kac, Edouardo, 1962-; medijska umetnost; digitalna književnost; elektronska poezija; tehnotekst